Botticelli Past and Present - Debenedetti, Ana; Elam, Caroline (UCL Press, 2019)
The recent exhibitions dedicated to Botticelli around the world show, more than ever, the significant and continued debate about the artist. Botticelli Past and Present engages with this debate. The book comprises four thematic parts, spanning four centuries of Botticelli's artistic fame and reception from the fifteenth century. Each part comprises a number of essays and includes a short introduction which positions them within the wider scholarly literature on Botticelli. The parts are organised chronologically beginning with discussion of the artist and his working practice in his own time, moving onto the progressive rediscovery of his work from the late eighteenth to the turn of the twentieth century, through to his enduring impact on contemporary art and design. Expertly written by researchers and eminent art historians and richly illustrated throughout, the broad range of essays in this book make a valuable contribution to Botticelli studies.